2020
DOI: 10.1186/s12886-020-01393-1
|View full text |Cite
|
Sign up to set email alerts
|

Sub-perfluoro-n-octane injection of ocular viscoelastic device assisted inverted internal limiting membrane flap for macular hole retinal detachment surgery: a novel technique

Abstract: Background: To evaluate the feasibility of a surgical technique using a sub-perfluoro-n-octane (PFO) injection of ocular viscoelastic device (OVD) to stabilize inverted internal limiting membrane (ILM) flap for the treatment of macular hole retinal detachment (MHRD). Methods: This study was a retrospective, consecutive, interventional case series. Patients who underwent MHRD surgery with sub-PFO injection of OVD to stabilize inverted ILM flap onto the macular hole (MH) were reviewed. The color fundus and optic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In addition, a recent comparative multicenter study demonstrated that limited vitrectomy is time-efficient and effective in removing epiretinal membrane without additional complications compared to complete vitrectomy [25]. Another study reported good outcomes of sub-perfluoro-n-octane injection as a viscoelastic agent in patients with macular hole retinal detachment [26]. e rate of retinal reattachment was numerically higher, but the difference was not significant, probably because of the small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent comparative multicenter study demonstrated that limited vitrectomy is time-efficient and effective in removing epiretinal membrane without additional complications compared to complete vitrectomy [25]. Another study reported good outcomes of sub-perfluoro-n-octane injection as a viscoelastic agent in patients with macular hole retinal detachment [26]. e rate of retinal reattachment was numerically higher, but the difference was not significant, probably because of the small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Then, perfluorocarbon liquid (PFCL; Alcon) was injected from the site of the ILM hinge to flatten the peeled ILM, and the ILM was returned to its original position by using the DDMS. To secure the repositioned ILM, an ophthalmic viscoelastic device (OVD; Viscoat; Alcon) was placed along the edge of the peeled ILM by using the sub-PFCL ophthalmic viscoelastic device injection (SPOT) technique 7,8 (See Video, Supplemental Digital Content 1, http://links.lww. com/IAE/B726, in which the PAIR and SPOT techniques are demonstrated).…”
Section: Surgical Techniquementioning
confidence: 99%
“…Similar results with high closure rates and improvements in vision have been reported in other similarly sized series with large MHs [ 58 60 ]. Maintaining the tissue within the hole may be difficult during air-fluid exchange, but use of perfluorocarbon or viscoelastic, as previously mentioned, can help tamponade the flap in place during this step of the surgery [ 61 , 62 ]. The pedunculated flap is where an ILM flap larger than the radius of the hole to the edge of the previous ILM peel is fashioned with the hinge at the edge of the previous ILM peel.…”
Section: Surgical Techniquesmentioning
confidence: 99%